2019
DOI: 10.1002/app.48450
|View full text |Cite
|
Sign up to set email alerts
|

Solubility parameter estimation and phase inversion modeling of bentonite‐doped polymeric membrane systems

Abstract: Effects of bentonite concentration on morphology and permeation characteristics of bentonite-doped polysulfone membranes were investigated. Solubility sphere for bentonite was constructed to estimate its solubility parameter. Thermodynamic modeling of phase inversion of this system was carried out using Flory-Huggins theory. The trade-off between thermodynamic and kinetic parameters was used to predict the membrane morphology for bentonite concentration varying from 0 to 5 wt %. The porosity of bentonitedoped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In the studies previously reported with various additives, thermodynamic and kinetic factors were opposing, i.e. thermodynamic enhancement was accompanied by kinetic hindrance or vice versa 27,28,30,31,41 . Sadrzadeh and Bhattacharjee have reported thermodynamic enhancement and kinetic hindrance due to the addition of polyethylene glycol and polyvinylpyrrolidone in polyethersulfone 41 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the studies previously reported with various additives, thermodynamic and kinetic factors were opposing, i.e. thermodynamic enhancement was accompanied by kinetic hindrance or vice versa 27,28,30,31,41 . Sadrzadeh and Bhattacharjee have reported thermodynamic enhancement and kinetic hindrance due to the addition of polyethylene glycol and polyvinylpyrrolidone in polyethersulfone 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of acetone on the thermodynamic parameter was quantified by calculating the thermodynamic parameter 31,41 . An increase in thermodynamic instability results in a shift of the binodal curve towards the polymer–solvent axis leading to a porous membrane morphology, whereas a shift away from the polymer–solvent axis signifies increased stability and a dense morphology 41,44 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations